Current Research in Thin Film Deposition Applications, Theory, Processing, and Characterisation - Birney, Ross (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Today, thin films are near-ubiquitous and are utilised in a very wide range of industrially and scientifically important areas. These include familiar everyday instances such as anti-reflective coatings on ophthalmic lenses, smartphone optics, photovoltaics, decorative, and tool coatings. A range of somewhat more exotic applications also exists, such as astronomical instrumentation (e.g., ultra-low loss dielectric mirrors and beam splitters in gravitational wave detectors, such as laser interferometer gravitational-wave observatory (LIGO)), gas sensing, medical devices and implants, and accelerator coatings (e.g., coatings for the large hadron collider (LHC), and compact linear collider (CLIC) experiments at European organization for nuclear research (CERN)). This Special Issue will provide a platform for researchers working in any area within this highly diverse field to share and exchange their latest research findings. The Special Issue contains novel studies encompassing material characterisation techniques, a range of thin-film coating deposition processes and applications of such technology.